Eight weeks of endurance training based on critical velocity associate with glutamine supplementation - Fontana, K. E.; Molina, G. E.; Kobayashi, L.; Rocco, G. F. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
The individualized prescription of exercise intensity is critical for obtaining satisfactory results in endurance training. Many practitioners of physical activity are associated with the use of glutamine expecting even better aerobic performance. Purpose: Analyze the aerobic capacity and body composition of a supervised endurance-training program associated with glutamine supplementation and placebo. Methods: Twenty-three physically active healthy young male (21.8 ± 2.1 years) volunteered to the study and underwent an endurance-training program based on critical velocity (CV) that consisted of three weekly sessions during eight weeks. CV was calculated by the slope of the linear regression between the time obtained through running tests of 400 and 2400 m (T400 e T2400). The peak oxygen output (VO2peak), oxygen uptake at anaerobic threshold (VO2AT) and at respiratory compensation point (VO2RCP) were determined by an incremental running treadmill test with breath by breath gas analyze. Blood lactate samples were used to determine the lactate threshold (LT) and the onset of blood lactate accumulation (OBLA). The experimental design was double blind controlled by placebo and the subjects were randomly assigned to two groups receiving either placebo (PLA, n=11) or glutamine (GLN, n=12) supplementation. Each oral supplement was given solved in a liquid sweetened vehicle once a day (0.003 g/kg). The tests were performed in random sequence, with a minimum interval of 48 hours between them. The training effect was compared by t-student test and the supplementation effect by ANOVA. Results: Independently of supplementation, after the eight-week endurance training program there were differences on all the variables except VO2RCP, VOBLA. When the training effect was observed on supplemented groups (PLA and GLN), both groups differed on T400, T2400, VO2AT, CV, VAT and no differences were found on body mass, VO2RCP, VLT and VOBLA. Percent body fat, VO2peak and VRCP differed only in the PLA group. The VO2peak differed between PLA and GLN (p=0.027) with higher values on the PLA group. CV was higher than other velocities measured in the study (VAT, VLT, VOBLA, VRCP). Conclusions: The critical velocity can be used as an aerobic performance measure, however does not replace the anaerobic threshold measured by direct methods. Moreover, glutamine supplementation did not show an ergogenic effect on aerobic output or on body composition in physically active young male after an eight-week endurance-training program.